Fabrication of ZnO@C foam: A flexible free-standing electrode for energy storage devices. (April 2020) - Fahimi, Zohre; Moradlou, Omran
Abstract: In this work, we have synthesized a flexible ZnO@C foam for its potential applications in energy production and storage devices based on the simple and versatile method. The fabricated ZnO@C foam exhibited enhanced capacitance compared to commercially available Ni foam. The fabrication process involves the synthesis of ZnO nanostructures, deposition of ZnO@C nanostructure on Ni foam, and finally, removing Ni substrate to have ZnO@C foam. Based on cyclic voltammetry, galvanostatic charge-discharge curves and electrochemical impedance spectroscopy, it was concluded that the ZnO@C foam has a suitable electron transfer rate and conductivity. ZnO@C foam provides a high areal specific capacitance of 1120 mF cm − 2 at a current density of 4 mA cm − 2 . The proposed flexible foam has potential applications in the fabrication of solid-state supercapacitors as well as fuel cells. Graphical abstract: Unlabelled Image Highlights: A flexible ZnO@C foam was fabricated as supercapacitor electrode/support. ZnO@C foam exhibits enhanced areal specific capacitance of 1120 mFcm − 2 at 4 mA cm − 2 . The foam provides improved charge transfer rate and high electrical conductivity. The asymmetric device delivers high energy density and excellent cycling stability. ZnO@C benefits high potential applicability in energy storage and production devices.